KRITIK TEORI HUKUM FEMINIS TERHADAP UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN: Suatu Upaya dalam Menegakkan Keadilan HAM Kaum Perempuan - Asnawi, Habib Shulton (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2011)
In Indonesia, women still suffer discrimination and injustice. This is supported by the persistence of gender-biased laws not giving the protection of the rights of women, such as Law No. 1 of 1974 about Marriage. Women's issues that was settled in the line of traditional Islamic law (classical) tending to be conservative and literal in understanding religious messages and doctrines, such as the patriarchal culture which puts women as beings lower position than men. Patriarchal culture which is done with legism legalized legislation in its application to the gender bias that is highly detrimental for women. The marginalization of women then occurs and is caused by the differences and gender inequalities that cause woman discomfort and not free. Therefore, all forms of injustice is a violation to Human Rights (HAM), a crime against human dignity and a form of discrimination that must be abolished.[Di Indonesia, perempuan masih mengalami diskriminasi dan ketidakadilan. Hal ini didukung oleh masih adanya undang-undang bias gender yang belum memberikan perlindungan terhadap hak-hak perempuan, seperti UU No.1 Tahun 1974 tentang Perkawinan. Isu-isu perempuan yang dimapankan di dalam UU tersebut sejalan Islam tradisional (klasik) yang cenderung konservatif dan literal dalam memahami pesan-pesan keagamaan dan doktrin-doktrin yang ada, seperti budaya patriarkhis, yang menempatkan perempuan sebagai makhluk yang lebih rendah kedudukannya dari pada laki-laki. Budaya patriarkhis yang dilakukan dengan kecenderungan legisme itu telah melegalisir peraturan perundang-undangan bias gender ke dalam penerapannya yang sangat merugikan perempuan. Marginalisasi perempuan kemudian terjadi dan disebabkan oleh perbedaan dan ketidakadilan gender yang menyebabkan ketidaknyamanan serta terbelenggunya kebebasan perempuan. Karena itu, segala bentuk ketidakadilan merupakan pelanggaran Hak Asasi Manusia (HAM), kajahatan terhadap martabat kemanusiaan dan bentuk diskriminasi yang wajib dihapuskan.]